Attribution of Blame in an Intimate Partner Violence Situation: The Effect of Victim Sexuality and Observer Sex. Issue 13 (July 2023) - Hill, Emily; Moreland, Georgia; Boduszek, Daniel; Debowska, Agata
Intimate partner violence (IPV) is an extensive public health concern, largely affecting women aged 20 to 24 years. Research suggests that bisexual women are more likely than heterosexual and homosexual women to be victims of IPV. Bisexual women are also more likely to be blamed for their abuse experiences after disclosing, a phenomenon known as victim blame attribution (VBA). However, very little VBA research recognizes bisexuality as a separate category. Therefore, the main aim of this quasi-experimental study was to investigate the role of female victim sexuality (bisexuality, homosexuality, and heterosexuality) and observer sex in the attribution of blame to the victim and perpetrator of IPV. Participants ( N  = 232; aged 18–24 years, M  = 21.05, SD  = 1.73) were randomly assigned into one of four conditions (heterosexual victim, bisexual victim with same-sex partner, bisexual victim with different-sex partner, homosexual victim), each containing a vignette portraying IPV within a relationship. Randomization checks were performed to ensure that participants in the four conditions did not differ significantly on underlying attitudes (institutional heterosexism (IH), aversive heterosexism (AH), heterosexual privilege (HP), sexist attitudes, just world beliefs) that may have affected their responses on outcome measures. Main analyses demonstrated that bisexual victims with a same-sex partner received the highest attribution of blame, whereas perpetrators in this condition received the lowest blame attribution. Male participants attributed significantly higher blame to victims than did female participants, regardless of victim sexuality. These findings substantiate the role of victim sexuality and observer sex in IPV blame attribution patterns. This research aimed to promote equality and rightful treatment to all victims of IPV regardless of their sexuality.